2018
DOI: 10.2478/alife-2018-0025
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Inter-Relations Between Fish Health and Stock Status of the Main Commercial Fish Species

Abstract: This paper aims to show the importance of knowing the health status of fish populations in their natural environment and its influence on fish stocks at the Romanian coast. To assess the interrelationship between fish health status and the state of stocks, the following fish species: turbot, sprat, anchovies and horse mackerel were analysed from the pathological point of view. Pathological analyses performed between 2015 and 2017 revealed the presence of infections caused by bacteria of the genus Aeromonas and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The signs of disease within a population are visible mainly after the installation of the state of stress, which reduces the resistance of organisms, and favors the outbreak of infectious, parasitic, or other diseases [42]. The manifestation of the disease phenomenon can cause growth, reproductive, and nutrition disorders at the population level and, in many cases, these epidemiologies can cause significant mortality in fish populations [43].…”
Section: Discussionmentioning
confidence: 99%
“…The signs of disease within a population are visible mainly after the installation of the state of stress, which reduces the resistance of organisms, and favors the outbreak of infectious, parasitic, or other diseases [42]. The manifestation of the disease phenomenon can cause growth, reproductive, and nutrition disorders at the population level and, in many cases, these epidemiologies can cause significant mortality in fish populations [43].…”
Section: Discussionmentioning
confidence: 99%
“…The fish caught in the lake have a bacillus load that is highly correlated with the load in lake water. Depending on the studies, Vibrio may be found [60] or not [61]), but the studies usually not try to correlate the occurrence of Vibrio simultaneously in the water and in the animals (but see [62] for example). The local residents frequently eat these fish raw or salted, without emptying them nor cooking them.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%